Determining the Clinical Depth of Anaesthesia Using a Pulse Oximeter and Investigating the Utility of the Perfusion Index in Pediatric Patients Undergoing Elective Surgery - Mouriya.S, Mouriya.S; Varshini.U, Monica; Mahendran, Uma Maheshwari; Chandrasekar, Gokulakrishnan; Yuvashree.K, Yuvashree.K (Journal of Neonatal Surgery, 2025)
The perfusion index (PI) is a reliable, non-invasive measurement obtained through pulse oximetry, effectively evaluating the depth of anaesthesia. Accurate assessment of anaesthesia depth in pediatric patients is crucial to mitigate complications such as intraoperative awareness or over-sedation. This study aimed to elucidate the correlation between the perfusion index (PI) and the clinical depth of anaesthesia in children undergoing elective surgical procedures. Additionally, the secondary objectives included evaluating the viability of the perfusion index as a monitoring tool and identifying factors contributing to its correlation with anaesthesia depth. The prospective observational study included 30 ASA pediatric patients aged 1 to 18 who underwent elective surgery under general anaesthesia. PI, heart rate (HR), and minimum alveolar concentration (MAC) measurements were taken during three critical phases: induction, maintenance, and emergence. Statistical analyses, including ANOVA, Levene's test, and correlation assessments, were conducted to ascertain associations and variability. The perfusion index exhibited statistically significant differences across the phases, demonstrating a peak during intubation (1.49 ± 0.20) and a trough during maintenance (1.07 ± 0.06). Furthermore, the PI displayed significant correlations with traditional measures of anaesthesia depth (HR: p = 0.002; MAC: p = 0.000). Therefore, the perfusion index strongly correlates with anaesthesia depth and maybe a valuable adjunctive monitoring tool in pediatric anaesthesia. Future studies involving larger sample sizes and comparisons with the bispectral index (BIS) must confirm its clinical applicability and identify potential confounding variables